Penerapan Cost Significant Model untuk Estimasi Biaya Proyek Rehabilitasi Ruang Kelas Belajar Pada Sekolah Negeri di Provinsi Maluku - Yesia Tahapary; Giovianne Friensty Marantika (JURNAL SIMETRIK, 2026)
This research examines the application of the Cost Significant Model (CSM) for estimating costs in classroom rehabilitation projects at public schools in Maluku Province. Given the region’s challenging geographical characteristics and the urgent need to improve educational infrastructure, accurate and efficient cost estimation methods are essential to prevent budget overruns and delays. The study collects and analyzes historical budget data from similar projects implemented between 2019 and 2024. By identifying the most significant cost items that contributed to the largest share to total expenses, the CSM allows for targeted resource allocation and effective risk mitigation. The research employs quantitative methods, including inflation adjustments and multiple regression analysis, to develop a predictive cost estimation model. Model accuracy is assessed using the Mean Absolute Percentage Error (MAPE), which shows a low average error of just 2.26%, confirming CSM’s effectiveness and consistency with previous studies. The findings demonstrate that CSM is both efficient and reliable for early-stage cost estimation in educational facility rehabilitation, especially when detailed project information is limited. The study recommends integrating CSM with conventional methods for optimal results as project data availability improves. Keywords: Construction Cost Estimation, Cost Significant Model, Project Management